EFL Teachers’ Professional Identity: A Critical Discourse Analysis - Jaime Marcial; Nora M. Basurto Santos (Profile: Issues in Teachers' Professional Development)
This study uses critical discourse analysis to explore the identities of three university English teachers. The research identifies ideological elements in language teaching and cultural transmission practices, following the post-structuralist literature on their role in shaping personal and professional identities. Findings are presented through extracts from narrative and semi-structured interviews, highlighting the political, cultural, academic, and personal subject positioning in teachers’ discourse. Critical discourse analysis elucidated the participants’ views on teaching and cultural practices on an ethical level. The conclusions propose a possible revision of their professional identities based on discourse analysis, contributing to a deeper understanding of teachers’ responsibilities towards language education. This was done with the construction of an interpretative profile with prescriptive aspects to enhance each participant’s teaching practice.